Dual active bridge synchronous chopper control strategy in electronic power transformer. Issue 3 (1st March 2014) - Zhang, Rui; Wang, Dan; Mao, Chengxiong; Lu, Jiming; Yang, Jiawei; Yi, Yang; Chen, Xun; Zhang, Junfeng
Abstract : The electronic power transformer (EPT) is a novel transmission and transformation device, which consists of a series connection of two voltage‐source H‐bridge converters and a DC–DC converter with high‐frequency isolation transformer. When applied to microgrids, EPT will not only deliver energy to loads from the utility grid but also inject some amount of excess power into the utility grid. Hence, the capability of bidirectional power flow is important for EPT, which depends on the DC‐link stage. The traditional synchronous chopper control for a dual active bridge (DAB) converter has some limitations in the application of bidirectional power flow area. This study proposes a novel synchronous chopper control strategy for the DAB converter to implement bi‐direction power flow, details the basic principle and steady‐state operation and presents the mathematical derivations. A three‐phase three‐stage circuit configuration of 10 kV/400 V bi‐direction EPT system based on the novel control DAB converter is designed, and corresponding control schemes for the system are discussed. The performance of this EPT system is validated by the MATLAB/Simulink‐based simulations and the laboratory prototype experiments.